Pharmacists' perceptions of their working conditions and the factors influencing this: Results from 5 Canadian provinces. (May 2020) - Tsao, Nicole W.; Salmasi, Shahrzad; Li, Kathy; Nakagawa, Bob; Lynd, Larry D.; Marra, Carlo A.
Introduction: Our previous study in British Columbia (BC) indicated that pharmacists have a poor perception of their working conditions. The objective of this study is to assess pharmacists' perceptions of their working conditions in 4 other Canadian provinces. Methods: This was a cross-sectional study across Alberta, New Brunswick, Prince Edward Island and Newfoundland and Labrador, using a survey adapted from the Oregon Board of Pharmacy. Data collected previously from BC were also included in the analyses. The survey was emailed to all pharmacist registrants. Respondents were provided with 6 statements and asked to rate their agreement with them, using a 5-point Likert scale. Statements were framed such that agreement with them indicated good perception of working conditions. Logistic regression analyses were used to study the relationship between workplace factors on perception of working conditions. Results: Pharmacists perceived their working conditions to be poor. Pharmacists indicated that they do not have time for break/lunch (48.3% of respondents), work in environments that are not conducive to safe and effective primary care (26.5%), are not satisfied with the amount of time they have to do their job (44.0%) and face shortage of staff (shortage of pharmacists: 33.7%, technicians: 36.4%, clerk staff: 30.3%). Significant factors associated with poor perception were workplace-imposed quotas, high prescription volume, working in chain pharmacies and long prescription wait times. Conclusion: A high percentage of Canadian pharmacists perceived their working conditions to be poor. Considering the patient-related consequences of pharmacists' poor working conditions and the system-related reasons identified behind it, we call for collaborative efforts to tackle this issue.